BIOLOGIA E DANOS DE OLIGONYCHUS YOTHERSI (MCGREGOR) (ACARI: TETRANYCHIDAE) EM ILEX PARAGUARIENSIS* - Alves, L.f.a. (2024)
The biology of the red spider mite Oligonychus yothersi (McGregor) was studied at Laboratório de Zoologia, Unioeste, Cascavel, State of Paraná, Brazil. Mites were taken from a laboratory stock colony on Paraguay tea leaves (Ilex paraguariensis) (St. Hil.). Leaf-discs were infested with adult females for oviposition, and after 24 hours only one egg was left on each disc. The study was carried out at 26º C and 14:10 hours of light:dark. Mites were evaluated twice daily. The duration of the immature phase was significativaly longer for males (11 days) than for females (10 days). Damage assessment was conduced on plants of a commercial area, where attacked leaves showed initially small purple spots on the dorsal surface along the central leaf vein but mostly at its base. The spots later coalesced, forming necrotic areas. The damaged leaves became wrinkled with the border turning down. Great numbers of mites at all life stages, exuviae and webbing were observed at scattered depressions on the upper leaf surface. The infestation affected leaf development; most of the infested leaves remained smaller than non-infested ones and dropped off prematurely.